ETIKA KOMUNIKASI ISLAM MASYARAKAT MUSLIM YANG DITERAPKAN DALAM MASYARAKAT MULTI AGAMA DI DESA SUKORENO KECAMATAN UMBULSARI KABUPATEN JEMBER: (Study Kasus Masyarakat Muslim di tengah kehidupan masyarakat Multi-Agama di desa Sukoreno-Umbulsari-Jember) - M. Sofiatul Iman (Indonesian Journal of Islamic Communication, 2020)
Religious harmony needs to be preserved in every aspect of life especially for the multi-religious community of Sukoreno Village. The diversity in that village has led to be the village of Bhineka Tunggal Ika. Muslims are the majoritas in that village. In the researcher's view, The reality of the harmony between Muslims and the Muslim community as the majority in Sukoreno village is there is an ethics of Islamic communication and communication patterns that is built in the community. So that life becomes orderly and balanced among individual.This research was qualitative through the type of case study research. this research reveals that the communication ethics of the Muslim community in the center of multi-religious community life in Sukoreno village is communication with respect, speaking as it is and not be exaggerating, using gentle speech and not impulsive. The pattern of communication which is built is two-way and linear communication.